REM versus Non-REM sleep disturbance specifically affects inter-specific emotion processing in family dogs (Canis familiaris) - Bolló, Henrietta (Sci Rep, 2020)
Dogs have outstanding capabilities to read human emotional expressions, both vocal and facial. It has also been shown that positively versus negatively valenced dog-human social interactions substantially affect dogs’ subsequent sleep. In the present study, we manipulated dogs’ (N = 15, in a within subject design) sleep structure by specifically disrupting REM versus Non-REM sleep, while maintaining equal sleep efficiency (monitored via non-invasive polysomnography). We found that both the number of awakenings as well as relative Non-REM (but not relative REM) duration influenced dogs’ viewing patterns in a task where sad and happy human faces were simultaneously projected with sad or happy human voice playbacks. In accordance with the emotion laterality hypothesis, the interaction between sound valence and Non-REM sleep duration was specific to images projected to the left (regardless of image-sound congruency). These results reveal the first evidence of a causal link between sleep structure and inter-specific emotion-processing in the family dog.